Role of human metapneumovirus, influenza A virus and respiratory syncytial virus in causing WHO-defined severe pneumonia in children in a developing country. - Asad Ali; Asif Raza Khowaja; Maaman Zahoor Bashir; Fatima Aziz; Sultan Mustafa; Anita Zaidi (PLoS ONE, 2013)
The role of respiratory viruses in causing severe, life threatening pneumonia in children in developing countries is not well established. Our study aims to determine the role of human metapneumovirus (HMPV), influenza A virus and respiratory syncytial virus (RSV) in children, aged 6 weeks to 2 years, hospitalized with WHO defined severe pneumonia (tachypnea plus any general danger sign or chest in-drawing) at a public sector hospital in Karachi, Pakistan.This study was conducted from November 2010 to September 2011 at Abbassi Shaheed Hospital, a large public tertiary care hospital in Karachi, Pakistan. Children admitted with WHO-defined severe pneumonia were enrolled and throat swabs were obtained to detect respiratory viruses using real time RT-PCR. Chest x-rays of all subjects were obtained and independently interpreted by two radiologists to diagnose radiologic pneumonia.169 children were enrolled. HMPV was detected in 24 (14.2%), influenza A virus in 9 (5.3%) and RSV in 30 (17.8%) children admitted with severe pneumonia. Of 9 patients with influenza A, 8 tested positive for H1N1. Viral etiology was found in 18% of radiologically confirmed pneumonia. HMPV infections peaked in February and April, influenza A was prevalent in January, June and November and RSV infections were most prevalent from June to September.HMPV, influenza A and RSV are common causes of WHO-defined severe pneumonia in hospitalized children in Karachi. Knowledge regarding the viral etiology of pediatric pneumonia and individual viral seasonality can help in the recommendation and implementation of appropriate management strategies.